التنبؤ بأهم القياسات الجسمية وعلاقته بسرعة ودقة أداء مهارة الطعن من الوثب بسلاح الشيش - عباس، عصام طالب; محمد، دعاء فوزي (جامعة بابل - كلية التربية الرياضية, 2015)
that has occurred at the level of achievement and performance in Game Fencing result of scientific efforts big of experts and specialists in the field of sports, which contributed to the development aspects of skill and tactical to penetrate and make it more difficult task of defending and attacking the opponent's turn, as the achievement of the lung of various distances in Altbarzelh instrumental in the win, where sources refer to the importance of accuracy the lung of jump distances and different angles to increase the success rate of the player attack swordsman and instructor Maha reached his skills will not be able to make a hero of the body is not qualified so inappropriate, have to be sporty, enjoying the pattern of my body appropriate to the type of sport that is practiced so that programs training her usefulness and importance of research reflected in the development of a set of bodily the measurements that serves as an indicator can be relied upon to choose the best and most promising players in the fencing, , And hopes to researchers in potential to benefit workers in the field of training by increasing the effectiveness of selection for measurements bodily appropriate and that would develop the skill of the lung of jump as one of the most important and the most difficult skills and the most widely used and effective in a game of fencing, and to find out what are the the measurements bodily variable predictor of the accuracy of the lung of jump Mar is one of the skills that confuse an opponent and affect it and increase the motivation of the player to get the touches many and here comes the role of the most important the measurements bodily own and their impact on the confusion defender technically in the speed and accuracy of the lung of the jump has felt researchers study this relationship, and enable coaches to rely on the scientific method correct in linking between the measurements bodily and accuracy of the lung of the jump was also used researchers the descriptive method his style survey and relationships connectivity for suitability in solving the problem of the research was chosen as the research sample way intentional for the squad Diyala in fencing,'s (30) player, representing the percentage (100%) The researchers introduced a questionnaire, to explore expert opinion to determine the most important the measurements bodily appropriate for the player who leads the lung of jump, and include (30) compared to physically After collecting the forms and discharge data were excluded measurements of physical and got on without percentage (100%) also used the researchers set of measurements and standardized tests to ensure the accuracy of the results according to the objectives of the study and the conclusions reached by the researchers that the the measurements bodily among a sample group appeared inconsistent relative to the sample optimal and there is little effect of some the measurements bodily performance parameters footwork offensive to the players, the research sample, there are obvious weakness in the accuracy the lung from jump, the subject of the study through the level that obtained by the research sample, and a weakness in percentage contribution of the most important the measurements bodily (weight, age, total length, length of stop, the length of the man) quickly and accurately the lung under discussion, and either of the recommendations reached by the researchers need to pay attention bodily measurements, especially in the early stages of the selection of players for the right investment and the economy in time and effort.
التطور الهائل الذي طرأ على مستوى الانجاز والأداء في لعبة المبارزة نتيجة الجهود العلمية الكبيرة للخبراء والمختصين في المجال الرياضي والتي ساهمت في تطوير الجوانب المهارية والخططية لاختراق وتصعيب مهمة الدفاع والهجوم المنافس المقابل , حيث أن تحقيق الطعن من مختلف المسافات في التبارز له دور فعال في تحقيق الفوز, حيث تشير المصادر الى أهمية دقة الطعن من الوثب من مسافات وزوايا مختلفة لزيادة نسبة نجاح اللاعب هجوم المبارز وان المدرب مها بلغت مهاراته لن يستطيع أن يصنع بطلا من جسم غير مؤهل لذلك لذى يلزم أن يكون الرياضي متمتعاً بنمط جسمي مناسب لنوع الرياضة التي يمارسها حتى تصبح برامج التدريب لها جدوى وأهمية البحث تتضح في وضع مجموعة من القياسات الجسمية التي تعد بمثابة مؤشر يمكن الاعتماد عليه في اختيار أفضل وانسب اللاعبين في المبارزة , ويأمل الباحثان في أمكانية إفادة العاملين في مجال التدريب من خلال زيادة فاعلية الانتقاء للقياسات الجسمية المناسبة والتي من شأنها تطوير مهارة الطعن من الوثب باعتبارها أحدى أهم وأصعب المهارات وأكثرها استخداما وفعالية في لعبة المبارزة , ولمعرفة ما هي القياسات الجسمية كمتغير متنبئ لدقة الطعن من الوثب آذ تعد من المهارات التي تربك الخصم وتوثر عليه وتزيد دافعية اللاعب للحصول على اللمسات الكثيرة وهنا يأتي دور أهم القياسات الجسمية الخاصة وتأثيرها على إرباك المدافع فنيا في سرعة ودقة الطعن من الوثب فقد ارتأى الباحثان دراسة هذه العلاقة , وتمكين المدربين في الاعتماد على الطريقة العلمية الصحيحة في الربط بين القياسات الجسمية ودقة الطعن من الوثب كما استخدم الباحثين المنهج الوصفي بأسلوبه المسحي والعلاقات الارتباطية لملائمته في حل مشكلة البحث وتم اختيار عينة البحث بالطريقة العمدية للاعبي منتخب ديالى في المبارزة والبالغ عددهم ( 30 ) لاعب، ويمثلون نسبة(100%) قام الباحثان بطرح استمارة استبيان , لاستطلاع رأي الخبراء لتحديد أهم القياسات الجسمية الملائمة للاعب الذي يؤدي الطعن من الوثب , وتتضمن (30) قياسا جسمياً وبعد جمع الاستمارات وتفريغ البيانات تم استبعاد القياسات الجسمية والتي حصلت على دون نسبة (100%) كما استخدم الباحثين مجموعة من القياسات والاختبارات المقننة لضمان دقة النتائج طبقاً لأهداف الدراسة ومن الاستنتاجات التي توصل لها الباحثان ان القياسات الجسمية لدى عينة فريق ظهرت غير متناسقة قياساً إلى عينة المثلى وهناك تأثير بسيط لبعض القياسات الجسمية في أداء المحددات المهارية الهجومية لدى لاعبي عينة البحث ,وهناك ضعف واضح في دقة الطعن من الوثب موضوع الدراسة وذلك من خلال المستوى الذي حصلت عليها عينة البحث , وضعف في نسبة مساهمة أهم القياسات الجسمية (الوزن، العمر، الطول الكلي، طول الكف ،طول الرجل) بسرعة ودقة الطعن قيد البحث, واما من التوصيات التي توصل لها الباحثين ضرورة الاهتمام بالقياسات الجسمية وخاصة في المراحل الأولى لانتقاء اللاعبين لاستثمارها الصحيح والاقتصاد بالزمن والجهد.
Keywords: القياسات الجسمية -- ألعاب القوى -- اللياقة البدنية -- الطعن من الوثب